2011
DOI: 10.1007/s11434-011-4891-3
|View full text |Cite
|
Sign up to set email alerts
|

Geometric algebra method for multidimensionally-unified GIS computation

Abstract: Seamless multidimensional handling and coordinate-free characteristics of geometric algebra (GA) provide means to construct multidimensionally-unified GIS computation models. Using the multivector representation for basic geometric objects within GA, we are able to construct adaptable unified geometric-topological structural models of a multidimensional geographical scene. Multidimensional operators found within the geometry, topology and GIS analysis are developed with basic GA operators. A unified computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Different dimensional geometry objects, such as the lines and planes shown in Figure 8, can be uniformly expressed with the outer product in CGA. In Euclidean space, representations of geometry objects are primarily based on coordinates, which causes problems such as complicated expression structure, non-uniform expression form in different dimensions, and unclear geometry meaning [47]. Geometric objects are expressed in CGA, and the outer product differs from the traditional methods, which are based on Euclidean geometry.…”
Section: Case Studiesmentioning
confidence: 99%
“…Different dimensional geometry objects, such as the lines and planes shown in Figure 8, can be uniformly expressed with the outer product in CGA. In Euclidean space, representations of geometry objects are primarily based on coordinates, which causes problems such as complicated expression structure, non-uniform expression form in different dimensions, and unclear geometry meaning [47]. Geometric objects are expressed in CGA, and the outer product differs from the traditional methods, which are based on Euclidean geometry.…”
Section: Case Studiesmentioning
confidence: 99%
“…DTINs and associated elements (points, segments, and triangles) can be uniformly represented with the multivector structure (Yuan et al 2011). Then the multivector representation can support multidimensionally unified computing with CGA operators (Yuan et al 2012).…”
Section: The Basic Ideamentioning
confidence: 99%
“…The result of the meet operator on two multivectors is also a multivector, which indicates the geometry of the intersection result. The intersection relations of geometric objects would adaptively change as the geometry types and positions change (Yuan et al 2012). Since the intersection with the meet product is unified and directly computed in a single mathematical framework, it can link the geometric representation and algebraic computation seamlessly.…”
Section: The Basic Ideamentioning
confidence: 99%
See 1 more Smart Citation
“…For each kind, the unitary realization, the non-unitary realization, and their connection by the corresponding similarity transformation are respectively discussed. Lie algebras have played an exciting and significant role in the development of various branches of physics and many other areas of science and technology [1][2][3][4][5][6][7][8][9][10][11]. In 1983, Kulish et al [12] showed that the algebra that governs the XXZHeisenberg spin model was a deformation of the Lie algebra SU(2), called nowadays SU q (2).…”
mentioning
confidence: 99%